2020
DOI: 10.1093/cercor/bhaa323
|View full text |Cite
|
Sign up to set email alerts
|

Temporally Distinct Roles for the Zinc Finger Transcription Factor Sp8 in the Generation and Migration of Dorsal Lateral Ganglionic Eminence (dLGE)-Derived Neuronal Subtypes in the Mouse

Abstract: Progenitors in the dorsal lateral ganglionic eminence (dLGE) are known to give rise to olfactory bulb (OB) interneurons and intercalated cells (ITCs) of the amygdala. The dLGE enriched transcription factor Sp8 is required for the normal generation of ITCs as well as OB interneurons, particularly the calretinin (CR)-expressing subtype. In this study, we used a genetic gain-of-function approach in mice to examine the roles Sp8 plays in controlling the development of dLGE-derived neuronal subtypes. Misexpression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 85 publications
1
2
0
Order By: Relevance
“…9 ). This linkage is consistent with reports that cells in mouse dLGE initially express SP8 and maintain TSHZ1 expression as they migrate via the LMS to become amygdala ITCs 19 , 25 . This developmental perspective suggests that these cells are not eccentric deviations from canonical spiny projection neuron development; instead, the LGE_FOXP2/TSHZ1 class converges on a similar striatal and amygdaloid projection neuron transcription profile despite its distinct origin.…”
Section: Reuse Of Ob Neurons In Primate Cerebrumsupporting
confidence: 92%
“…9 ). This linkage is consistent with reports that cells in mouse dLGE initially express SP8 and maintain TSHZ1 expression as they migrate via the LMS to become amygdala ITCs 19 , 25 . This developmental perspective suggests that these cells are not eccentric deviations from canonical spiny projection neuron development; instead, the LGE_FOXP2/TSHZ1 class converges on a similar striatal and amygdaloid projection neuron transcription profile despite its distinct origin.…”
Section: Reuse Of Ob Neurons In Primate Cerebrumsupporting
confidence: 92%
“…2k, Supplementary Movies 1 and 2). Our analysis also revealed limited overlap (~13%) at P7 of the PL Dcx + cells and Tshz1, which primarily marks dorsal lateral ganglionic eminence (dLGE)-derived cells that populate the ITCs [49][50][51] . This fraction significantly decreased with age (Extended Data Fig.…”
Section: The Pl Contains a High Density Of Tbr1 + Excitatory Neuronsmentioning
confidence: 80%
“…Our prior single nuclei RNA-sequencing studies further identified BCL11B/CTIP2 as a putative PL marker in humans 7 . We assessed FoxP2 and Tshz1 expression, which label the ITCs [49][50][51] , the dense GABAergic cell clusters adjacent to the BLA, and SatB2, a marker of the vEN [52][53][54] . We also examined expression of the pallial marker Pax6 55 , and Sp8, a marker of migratory interneurons in the RMS 56 .…”
Section: The Pl Contains a High Density Of Tbr1 + Excitatory Neuronsmentioning
confidence: 99%